2023
DOI: 10.1177/08982643221147637
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Employment–Family Trajectories and Well-Being in Later Life: Evidence From France

Abstract: Objective: Previous research in various countries has found that employment–family trajectories characterized by early or single motherhood, or weak ties to employment, are associated with poor well-being among older women. Our paper explores whether this differs (1) in France, characterized by a high female employment rate and supportive family policies; (2) across dimensions of well-being. Method: We used the Health and Occupational Itinerary survey to identify 10 common patterns of employment–family traject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…However, this does not apply to women who had their first child around 24 years; they reported more anxiety, poorer perceived health, and lower social support compared with older full-time working women. 16 An additional study demonstrated that earlier transition into parenthood was significantly associated with increased metabolic risk regardless of career attachment or marital stability. 17 Therefore, it might be imperative to distinguish between unemployed postpartum mothers who have consciously chosen to take time off work for a relatively short period to care for their newborn and those who have been unem-Telomeres are the protective caps at the end of chromosomes, which protect genetic material and shorten with each cell division.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…However, this does not apply to women who had their first child around 24 years; they reported more anxiety, poorer perceived health, and lower social support compared with older full-time working women. 16 An additional study demonstrated that earlier transition into parenthood was significantly associated with increased metabolic risk regardless of career attachment or marital stability. 17 Therefore, it might be imperative to distinguish between unemployed postpartum mothers who have consciously chosen to take time off work for a relatively short period to care for their newborn and those who have been unem-Telomeres are the protective caps at the end of chromosomes, which protect genetic material and shorten with each cell division.…”
mentioning
confidence: 98%
“…Mothers’ age might play a role here; a recent study in France found that consistently having a full-time job is generally linked to enhanced well-being. However, this does not apply to women who had their first child around 24 years; they reported more anxiety, poorer perceived health, and lower social support compared with older full-time working women 16 . An additional study demonstrated that earlier transition into parenthood was significantly associated with increased metabolic risk regardless of career attachment or marital stability 17 .…”
mentioning
confidence: 99%